EDUCATION VALUE AND FOLKLORE CULTURE PAU-PAU RIKADONG PRINCESS TADDAMPALlE - -, Juanda (Journal of Humanity, 2013)
This article elaborates education value and cultural in folklore Pau-pau Rikadong, Princess We Taddampalie which is one of folklore in South Sulawesi. This research problem is education values and culture what is there is in folklore Pau-pau Rikadong?